Analisis Pengaruh Penerapan Prinsip Syariah dan Inovasi Produk terhadap Kinerja Keuangan Bank Syariah di Indonesia - Muhammad Nabil Hisyam Ayyubi; Moch Mukhsin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the impact of sharia principles implementation and product innovation on the financial performance of Islamic banks in Indonesia. Using a quantitative approach through regression analysis, the study reveals that consistent adherence to sharia principles and relevant product innovation significantly affect financial performance. Partial tests show that sharia principles significantly influence customer trust and satisfaction, while product innovation contributes to enhancing competitiveness in the digital era. Simultaneously, these two variables strongly impact financial performance, with the regression model explaining 74% of the variance in financial performance. This study highlights the importance of synergy between sharia principles and product innovation in supporting the sustainability of the Islamic banking industry in Indonesia.